A single adenovirus‐mediated relaxin delivery attenuates established liver fibrosis in rats. (January 2016) - Kim, Ja Kyung; Lee, Jung Il; Paik, Yong‐Han; Yun, Chae‐Ok; Chang, Hye Young; Lee, Su Yeon; Lee, Kwan Sik
Abstract: Background: Liver fibrosis is characterized by an excess accumulation and repressed degradation of extracellular matrix. Although methods of alleviating already established liver fibrosis have scarcely been reported, continuous relaxin (RLX) infusion has demonstrated some promising results. In the present study, we investigated whether a single adenoviral delivery of RLX would attenuate established liver fibrosis in rats. Methods: Rats were given thioacetamide (TAA) for 8 weeks and infected once with either RLX‐expressing adenovirus (TAA + RLX) or control virus (TAA + Vector) via the tail vein. They were sacrificed either 3 days or 3 weeks after adenovirus infection. Results: Morphometric analysis of picrosirius red stained area demonstrated that the TAA + RLX group had significantly decreased fibrosis at week 3 when liver fibrosis of the TAA + Vector group remained unchanged. Although the liver and serum RLX levels were elevated on day 3 and reversed by week 3, expression of RLX receptor ( Rxfp1 ; relaxin‐like family peptide receptor‐1 ) in TAA + RLX rats was sustained and elevated. The production of tissue cyclic adenosine monophosphate, which is a second messenger of activated Rxfp1, was still enhanced in the TAA + RLX group by week 3. Expression of lysyl oxidase homolog 2, which contributes to collagen cross‐linking and is up‐regulated by TAA treatment, was significantly decreased by week 3 in the TAA + RLX group. Expression of tissue inhibitor of metalloprotiase‐2 was alleviated in the TAA + RLX group at week 3, whereas that of TAA + Vector rats was still elevated. Conclusions: A single adenoviral delivery of RLX in the liver attenuated established hepatic fibrosis by suppressing collagen cross‐linking and enhancing collagen degradation. Copyright © 2016 John Wiley & Sons, Ltd.